Accrual Quality, Corporate Governance, and Performance - Fambudi, Imam Nurcahyo; Murwaningsari, Etty (Countable (Contemporary Business and Sustainability Science), 2024)
This study investigates the effect of accrual quality and corporate governance on performance. The company's performance is in proxy with an accounting base represented by asset return while the market base is represented by Tobin-q. using a sample of manufacturing companies included in the 100 companies with the largest capitalization according to IICD obtained 57 observations consisting of 19 companies per year from 2015-2017. This study used statistical analysis, using a purposive sampling method with multiple regression. It was found that corporate governance has a positive and significant influence on accounting performance, while the quality of accrual and corporate governance has a positive and significant influence on market performance.